Burkina Faso : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
During most of the 1980s, Burkina Faso followed a development strategy based on central planning and pervasive controls that resulted in large macroeconomic imbalances. The consumer price index in Burkina Faso is influenced not only by the supply of domestically produced foodstuff, mainly cereals, but also by the fixed exchange rate regime. Monetary policy is conducted within the framework of the West African Economic and Monetary Union. The reform strategy has revived the cotton sector. Both transportation and labor costs have been reduced for the cotton sector.